Mesenchymal stromal cell‐derived extracellular vesicles for regenerative therapy and immune modulation: Progress and challenges toward clinical application. (14th August 2019) - Allan, David; Tieu, Alvin; Lalu, Manoj; Burger, Dylan
Abstract: Extracellular vesicles (EVs) derived from mesenchymal stromal cells (MSCs) have emerged as a promising form of regenerative therapy and immune modulation. Fundamental advances in our understanding of MSCs and EVs have allowed these fields to merge and create potential cell‐free therapy options that are cell‐based. EVs contain active cargo including proteins, microRNA, and mRNA species that can impact signaling responses in target cells to modify inflammatory and repair responses. Increasing numbers of preclinical studies in animals with various types of injury models have been published that demonstrate the potential impact of MSC‐EV therapy. Although the emergence of registered clinical protocols suggests translation to clinical application has already begun, several barriers to more widespread clinical adoption remain. In this review, we highlight the progress made in MSC‐derived small EV‐based therapy by summarizing aspects pertaining to the starting material for MSC expansion, EV production, and isolation methods, studies from preclinical models that have established a foundation of knowledge to support translation into the patient setting, and potential barriers to overcome on the path to clinical application. Abstract : Cumulative number of published articles investigating the therapeutic efficacy of extracellular vesicles derived from mesenchymal stem cells in preclinical animal models of disease.*Number of articles published in 2018 was extrapolated based on the total number of published articles until May of 2018.